2013
DOI: 10.1136/bmjqs-2013-002395
|View full text |Cite
|
Sign up to set email alerts
|

Using ‘nudge’ principles for order set design: a before and after evaluation of an electronic prescribing template in critical care

Abstract: The presentation of choices within an electronic prescribing system influenced the delivery of evidence-based interventions in a predictable way and the effect was well sustained. This approach has the potential to enhance the effectiveness of computerised order sets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 21 publications
0
66
0
Order By: Relevance
“…[38,46,50,51,59,70,71,72] Six studies showed improvement of user uptake and satisfaction. In a study by Chow and co-workers, the proportion of times when CDS was used when antibiotics were prescribed increased from 23% in phase (1) to 38% in phase (2) and to 87% in phase (3).…”
Section: Resultsmentioning
confidence: 99%
“…[38,46,50,51,59,70,71,72] Six studies showed improvement of user uptake and satisfaction. In a study by Chow and co-workers, the proportion of times when CDS was used when antibiotics were prescribed increased from 23% in phase (1) to 38% in phase (2) and to 87% in phase (3).…”
Section: Resultsmentioning
confidence: 99%
“…The careful design of default options has been shown to dramatically change prescribing behaviour and improve compliance with evidence-based interventions. [18][19][20] Although many default settings exist within the ICU, their role is poorly understood, and unless careful attention is applied to them they can result in harm, 21 The default settings on ventilators lead patients to be ventilated on lower TVes for a persistent period of time. Patients who were on default ventilators had significantly lower TVes than patients who were not.…”
Section: Discussionmentioning
confidence: 99%
“…When choice architecture is neglected, defaults may lose power [19,40,41]. Therefore, for defaults to exert their maximal and intended effects, they must be created and implemented with clear attention to exactly how they may change behaviors.…”
Section: Recently Examined Use Of Defaults In Critical Care Medicinementioning
confidence: 99%